A Mouse Model of Ulcerative Cutaneous Leishmaniasis by Leishmania (Viannia) panamensis to Investigate Infection, Pathogenesis, Immunity, and Therapeutics (2022)
ABSTRACT: A mouse model of cutaneous leishmaniasis (CL) by Leishmania (Viannia) panamensis (L(V)p) that reproduces the characteristics of the human disease remains elusive. Here we report the development of a CL model that uses a mouse-adapted L(V)p isolate to reproducibly induce a dermal disease with a remarkable similarity to human CL. BALB/c mice infected intradermally in the ear with 105 stationary UA-946 L(V)p promastigotes develop a progressive cutaneous disease that exhibits the typical ulcerated lesions with indurated borders observed in CL patients. Although most of parasites in the inoculum die within the first week of infection, the survivors vigorously multiply at the infection site during the following weeks, paralleling disease appearance and aggravation. Regional lymphadenopathy as well as lymphatic dissemination of parasites to draining lymph nodes (dLN) was evidenced early after infection. Viable parasites were also isolated from spleen at later timepoints indicating systemic parasitic dissemination, but, strikingly, no signs of systemic disease were observed. Increasing numbers of myeloid cells and T lymphocytes producing IFNγ and IL-4 were observed in the dLN as disease progressed. A mixed adaptive L(V)p-specific T cell-mediated response was induced, since ex vivo recall experiments using dLN cells and splenocytes revealed the production of type 1 (IFNγ, IL-2), type 2 (IL-4, IL-13), regulatory (IL-10), and inflammatory (GM-CSF, IL-3) cytokines. Humoral adaptive response was characterized by early production of IgG1- followed by IgG2a type of L(V)p-specific antibodies. IFNγ/IL-4 and IgG2a/IgG1 ratios indicated that the initial non-protective Th2 response was redirected toward a protective Th1 response. In situ studies revealed a profuse recruitment of myeloid cells and of IFNγ- and IL-4-producing T lymphocytes to the site of infection, and the typical histopathological changes induced by dermotropic Leishmania species. Evidence that this model is suitable to investigate pharmacological and immunomodulatory interventions, as well as for antigen discovery and vaccine development, is also presented. Altogether, these results support the validity and utility of this novel mouse model to study the pathogenesis, immunity, and therapeutics of L(V)p infections.